Quarter life crisis dan toxic relationship pada mahasiswa Studi Kasus: Mahasiswa Se- Jabodetabek Raya di Malang: Quarter life crisis and toxic relationships among students; Case Study of Greater Jakarta in Malang - Aisyah Wulandari; Julaihah , Umi (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2024)
This quarter life crisis arises when students are faced with academic pressure, questions about life goals, and uncertainty about the future. Quarter life crisis can be an entry point for students to become involved in toxic relationships. The purpose of this research is to determine the relationship between the quarter life crisis and students who experience toxic relationships. This research uses a mixed method approach which combines quantitative and qualitative research. The population that is the subject of this research is Jabodetabek students who are currently studying in Malang. The sampling technique used was non-probability sampling which involved 133 respondents. The measurement instruments applied include the quarter life crisis and toxic relationship scales. The analytical method applied is simple regression analysis using IBM SPSS version 22 software for Windows. The findings of this research reveal that the majority of students who experience quarter life crises and toxic relationships are women. This is based on (p = 0.000 < 0.05). With a coefficient of determination (R Square) of 0.427, which means that the influence of the independent variable (quarter life crisis) on the dependent variable (toxic relationship) is 42.7%, while the remainder is influenced by other factors outside the variables of this research.